Archaeological Research on the Closest Suburban Area of Ancient Theodosia. Investigations of the Theodosian Archaeological Expedition of the State Hermitage Museum in 2019–2022 - Akhmadeeva, Maria (Hyperboreus, 2024)
The paper offers preliminary results of the archaeological investigations of the Theodosian Archaeological Expedition of The State Hermitage Museum. The expedition has been exploring the closest suburban area of the ancient city of Theodosia since 2017. The point of particular interest is located 1.5 km to the south of the ancient city’s supposed acropolis. Survey studies using geophysical methods revealed the traces of quite dense building structures on a significantly sized territory. One of these building complexes, named Building A, was found in 1982 and has been explored since 2019 by the Hermitage expedition. Part of a large building currently containing about 150 m2 was unearthed. Finds discovered during the excavations enable us to date Building A to the period from the turn of the fifth to the fourth century BC up to the end of the fourth or the very beginning of the third century BC. Building A was reconstructed at least twice during its lifetime. During the first stage, the structure functioned as a vinery: parts of two pressing platforms and a space for placing pithoi indicate it clearly.